Publication performance in the field of physical medicine and rehabilitation in Turkey: A missed field in TUBITAK Field Based Competency Analysis Report 2020 - YAĞCI, İLKER (My University, 2022)
The Scientific and Technological Research Council of Turkey (TUBITAK) has recently published “Field Based Competency Analysis of Turkish Universities 2020” report, which evaluates research performances of universities.[1] In the report announced by TUBITAK, 20 main research areas and 131 subresearch areas were identified. In the determination of research areas, field classification of the previous 2016 report was mainly considered for the continuity of the work. Subsequently, the following were also taken into consideration: global trends, national policies and strategies, opinions of expert members in advisory and group executive board, research centers and institutes of TUBITAK “All Science Journal Classification,” and educational areas of universities. However, despite the existence of the rehabilitation subfield, evaluation of research performances in the physical medicine and rehabilitation (PMR) field could not be found in the report. In this letter, we would like to provide a brief report of publications from Turkey in the field of PMR.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Medicine; Health Sciences; Internal Medicine Sciences; Physical Medicine and Rehabilitation; REHABİLİTASYON; Klinik Tıp; Klinik Tıp (MED); REHABILITATION; CLINICAL MEDICINE; Clinical Medicine (MED); Kayropraktik; Rehabilitasyon; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Chiropractics; Rehabilitation; Physical Therapy, Sports Therapy and Rehabilitation